Memaknai Toleransi Secara Teologis Sebagai Upaya Moderasi Beragama - Henri Sirangki; Mariani Rombe Payung; Yusri; Alfrisa Ayo’ Payung Allo (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2023)
Tolerance and Moderation are phrases that have become the attention of researchers so that many of them make them the topic of writing. Although this phrase is not a foreign thing, its implementation both individually and communally in the life of a pluralistic society is still difficult to translate. Therefore, the purpose of this study is to explain how to live tolerantly in the midst of religious pluralism as an effort to moderate religion. The method used is descriptive qualitative where data collection is through literature. The results achieved are presented in a descriptive narrative form. Tolerance is an attitude of openness and sincere acceptance of differences. Meanwhile, religious moderation is a moderate attitude that becomes a reference in religion. The Old Testament explains that from the beginning God created differences. The life of the ancestors of the Israelites who lived among foreign nations is proof that human life was originally lived in difference. Their life in the midst of national and religious pluralism does not cause estrangement, but becomes a blessing for them, even though they have become a great nation. The New Testament records how one should live tolerantly in a pluralistic society, even Jesus himself became an actor of tolerance and moderated radical attitudes by extreme Judaism. So theologically, the meaning of tolerance is found, that from the beginning there were differences. In an effort to moderate religion, there must be mutual respect among adherents of different religions, so that harmony can be maintained.